When are employers interested in electronic performance monitoring? Results from a factorial survey experiment - Luisa Wieser; Martin Abraham; Claus Schnabel; Cornelia Niessen; Mauren Wolff (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2023)
This paper examines supervisors' considerations about (not) using monitoring technologies to keep track of subordinates and their work performance. We conduct a factorial survey experiment. The hypothetical descriptions of workplace situations - so-called vignettes - create a situation where the surveyed supervisor is faced with a new team of subordinates and a given technology that can be used to track employees at work. Several components of the situation are randomly varied across vignettes and respondents. We find that supervisors are less interested in using monitoring technologies if the monitoring technology targets people rather than tasks and if the time effort for the supervisor is high. Supervisors' monitoring interest increases if their subordinates interact with sensitive firm data and the data evaluation is AI supported. Thus, our results confirm that supervisors take the costs and benefits of electronic performance monitoring into consideration regarding their attitude towards monitoring technologies at work. – – Dieser Beitrag analysiert die Überlegungen von Vorgesetzten, ob sie Überwachungstechnologien einsetzen sollen, um ihre Untergebenen und deren Arbeitsleistung zu beobachten. Wir führen einen faktoriellen Survey (Vignettenstudie) durch. Hypothetische Beschreibungen von Arbeitsplatzsituationen erzeugen eine Situation, wo der/die befragte Vorgesetzte einer neuen Gruppe von Mitarbeitenden und einer einsetzbaren Überwachungstechnologie gegenübersteht. Mehrere Merkmale der Arbeitsplatzsituation werden über die Vignetten und Befragten hinweg zufällig variiert. Es zeigt sich, dass Vorgesetzte weniger Interesse am Einsatz von Überwachungstechnologien haben, wenn letztere v.a. Beschäftigte und weniger Tätigkeiten überwachen und wenn der Zeitaufwand für sie hoch ist. Das Überwachungsinteresse der Vorgesetzten nimmt zu, wenn ihre Untergebenen mit sensiblen Firmendaten umgehen und die Datenauswertung KI-gestützt erfolgt. Insgesamt bestätigen unsere Ergebnisse, dass Vorgesetzte bei ihren Überlegungen und Entscheidungen die Kosten und Nutzen einer elektronischen Überwachung einbeziehen.
Keywords: M50; D22; J01; 330; employee performance monitoring; workplace technology; factorial survey experiment; Germany